Edward Said: Orientalism and Occidentalism - Lary, Diana (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 2006)
AbstractTwenty-five years after the appearance of Orientalism, Edward Said’s ideas still have great importance, both in relations between the West and the Middle East, and in settings that Said did not address directly. This paper looks at orientalism between Asian states, between Asia and the West, and within China.